Black Box Testing of Futsal Field Rental Information Systems Using Automated Testing Method - Fauzan Asrin (Universitas Bina Darma, 2023)
A pivotal aspect of software development is testing, which serves as the final phase preceding the release of a software or information system. The realm of software testing encompasses a diverse array of methods, and within the scope of this investigation, the focus is on black box testing. In pursuit of this objective, the study leverages the capabilities of the Katalon Studio for Automated Testing. Its application is directed towards evaluating the functionality of an information system dedicated to the rental of futsal fields in the city of Singkawang. The essence of this examination lies in affirming the integrity of each feature and menu that constitutes the futsal field rental information system. This validation process is integral to ensuring that the system aligns seamlessly with the requisites of its users. The culmination of these testing endeavors culminates in the confirmation that the information system harmoniously resonates with user expectations. Consequently, it stands primed for implementation and subsequent release, signifying the attainment of a pivotal milestone in its development journey.